Clinical manual for the psychiatric interview of children and adolescents - Cepeda, Claudio 1942- (IG library, 2010)
Clinical Manual for the Psychiatric Interview of Children and Adolescents shows how to focus the exploration of common psychiatric syndromes while offering guidance in such matters as general principles of interviewing, use of the AMSIT in mental status examinations, and evaluation of both internalizing and externalizing symptoms.